2017
DOI: 10.18632/oncotarget.15533
|View full text |Cite
|
Sign up to set email alerts
|

CXCR1/2 pathways in paclitaxel-induced neuropathic pain

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a type of neuropathic pain that represents a frequent and serious consequence of chemotherapy agents. Over the last years, significant progress has been achieved in elucidating the underlying pathogenesis of CIPN. The interference of taxanes with microtubule has been proposed as a mechanism that leads to altered axonal transport and to permanent neurological damages. The inflammatory process activated by chemotherapeutic agents has been considered as a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 74 publications
(89 reference statements)
7
37
0
Order By: Relevance
“…Interestingly, a low incidence and severity of grade 3 and 4 peripheral neuropathy was observed compared with published studies with weekly paclitaxel [25]. A possible role of reparixin in reducing this common adverse reaction to paclitaxel is being investigated in experimental models [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a low incidence and severity of grade 3 and 4 peripheral neuropathy was observed compared with published studies with weekly paclitaxel [25]. A possible role of reparixin in reducing this common adverse reaction to paclitaxel is being investigated in experimental models [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Caspase signaling is also found to contribute to PIPN, leading to the generation of reactive oxygen species (ROS), as well as potential apoptosis (Park et al, 2004 ). Additionally, pathways activate inflammatory cytokines, such as TNF-α, MAPK, and CX3CL1, are involved with CIPN as well (Cavaletti et al, 2000 ; Zhang et al, 2010 ; Brandolini et al, 2017 ). Moreover, recent evidences indicated that activation of TRPV1 during chemotherapy sensitizes pain pathways.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, low dose of Paclitaxel produces hypersensitivity pain including allodynia and hyperalgesia. Neurotoxicity caused by Paclitaxel is attributed to alteration of microtubule structure leading to increased microtubule stability by increasing acetylated α-tubulin causing neuropathic pain, but it has been recently indicated that Paclitaxel triggers the activation of IL-8 signaling in DRG neurons in culture [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we wanted to test the hypothesis that Paclitaxel-induced neuropathic pain can be counteracted by the probiotic formulation of DSF. To this purpose, the biomolecular pathways involved in chemotherapy induced peripheral neuropathy, already described by us in a previous work [ 21 ], were investigated.…”
Section: Introductionmentioning
confidence: 99%